Wordwall-Assisted TGT Learning Models in The Solar System Materials: Its Impact on Improving Students' Concept Understanding - Astuti, Aldita Tasya; Zulirfan, Zulirfan; Ernidawati, Ernidawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this study was to evaluate the impact of using the Teams Games Tournament (TGT) cooperative learning model on the conceptual understanding of seventh grade junior high school students. Experimental research with a quasi-experimental design